2023
DOI: 10.7759/cureus.34430
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy Versus Platelet Rich Plasma Injection in Patients of Chronic Plantar Fasciitis: A Randomized Controlled Trial From a Tertiary Center of Eastern India

Abstract: IntroductionPlantar fasciitis is a degenerative condition of the plantar fascia that leads to heel and sole pain. Physical modalities, physiotherapy, medication, and orthoses have been tried before as treatments. Extracorporeal shockwave therapy (ESWT) and the injection of autologous platelet-rich plasma (PRP) are generally effective in the treatment of plantar fasciitis, which might be resistant to other conservative measures. The present study compares the efficacy of ESWT and PRP injection in respect of sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…2,9,12,16,21,31,32,40 However, our results show that PRP was superior in reducing pain outcomes when compared with ESWT. In fact, 6 of the 7 analyzed studies 6,11,13,27,33,38 showed better pain improvement in the PRP group, with the remaining study showing no significant differences between PRP and ESWT. 36 However, one must note that this study had a high risk of bias in our study because the randomized controlled trial was not blinded.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2,9,12,16,21,31,32,40 However, our results show that PRP was superior in reducing pain outcomes when compared with ESWT. In fact, 6 of the 7 analyzed studies 6,11,13,27,33,38 showed better pain improvement in the PRP group, with the remaining study showing no significant differences between PRP and ESWT. 36 However, one must note that this study had a high risk of bias in our study because the randomized controlled trial was not blinded.…”
Section: Discussionmentioning
confidence: 94%
“…Six randomized controlled trials met inclusion criteria and were included in this meta-analysis. 11,13,27,33,36,38 Altogether these studies included 214 subjects in the PRP group and 218 subjects in the ESWT group. The characteristics of the included studies are summarized in Table 1.…”
Section: Study Characteristics and Descriptionsmentioning
confidence: 99%
“…It is a fact that there are trials based on a single infiltration of PRP. In some of them, a 3 mL dose was used [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] which is 50% more PRP than the PRP used in the trial (2 mL) presented in this paper. Other authors used larger doses, such as 4 mL of PRP [ 55 ] or even 5 mL of PRP in a single infiltration [ 56 ], which represents 150% more PRP than used in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to stress is that before infiltrating the feet diagnosed with chronic PFS, some authors perform either a posterior tibial nerve block [ 7 , 46 ] or local anaesthesia at the infiltration site [ 7 , 47 , 51 , 57 , 58 ] and this is a totally different procedure. In this trial, there was no nerve block or anaesthesia, and the infiltration area was only sprayed with chloroethyl Chemirosa with the exclusive purpose of reducing skin sensitivity at the time of the puncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation